Cosmic sin [videorecording (DVD)] - Drake, Edward; Large, Corey; Large, Corey; Large, Corey; Willis, Bruce, 1955-; Grillo, Frank, 1963-; Lee, Brandon Thomas (Paramount Home Entertainment, 2021)
In the year 2524, four centuries after humans started colonizing the outer planets, retired Gen. James Ford gets called back into service after a hostile alien fleet attacks soldiers on a remote planet. The threat against mankind soon escalates into an interstellar war as Ford and a team of elite soldiers try to stop the imminent attack before it's too late.